Evaluation of the prospects of using solar thermal air-conditioning systems in Saudi Arabia - Islam, Mazharul; Amin, Muhammad Ruhul; Ani, Farid Nasir (Trans Tech Publications, Switzerland, 2014)
Saudi Arabia is endowed with abundant solar energy which is readily available from the sun. Solar energy is one of main renewable energy sources and it can be harnessed for an array of applications including heating, cooling and generation of electricity. Due to its hot climate and relatively high purchasing power capability of the general population, Saudi Arabia has a huge demand for air-conditioning (cooling) appliances. Currently these appliances are mainly powered by electricity generated by conventional sources using fossil fuels. Solar air-conditioning system is an emerging technology which relies on the sun for meeting the energy demand. One attractive feature of this system is that the high demand for space cooling by air-conditioning equipment coincides with the abundant availability of solar irradiation during the long summer months. Currently there are several types of solar air-conditioning systems, including the absorption, adsorption and desiccant systems. Each system has its merits and demerits. In this paper, the prospects of using absorption solar thermal air-conditioning systems for space cooling in Saudi Arabia are given. Â© (2014) Trans Tech Publications, Switzerland.